Evaluation on durian var. Musang King pollination compatibility regarding high fruit set - Su, Nurlisa Sy Ei; Ismail, Mohd Firdaus (Universiti Putra Malaysia Press, 2022)
Durian or Durio zibethinus of variety Musang King is growing in popularity and with high international demands. With the ever-increasing demands for fruits, growers are exploring ways to maximize production by looking at the feasibility of planting single or mono varieties in a planting area. Previous investigations revealed that many durian varieties are self-incompatible, and the condition varies from one variety to another. Against this background, the present study evaluated Musang King’s compatibility status in fruit sets. The study was conducted in Raub, Pahang, from 2017 through 2018 with five different pollination treatments. Crossing Musang King with D24 showed the highest fruit set rate of 16.28% at harvest and suggested this variety is self-incompatible. Observations on the flowering process revealed that Musang King possessed herkogamy condition, which posed a morphological barrier to self-pollination. The study proposes that Musang King is best planted in a multi-variety planting system instead of mono-variety to achieve a higher rate of fruit sets.